Thermographic Monitoring of Laser Cutting Machine - Paolo Bison (Proceedings, 2019)
Computer Numerical Controlled (CNC) laser cutting tools are developing as an alternative to conventional cutting systems thanks to increased accuracy, non-contact processing, higher productivity, less energy demand. An IR camera is utilized to monitor the laser cutting process of a steel plate. Even though the process is very complicated an analytical solution of the temperature field generated on a slab by a point source moving along one direction of the plate surface is provided in order to interpret the temperature field experimentally obtained by the IR camera.